2016
DOI: 10.1371/journal.pone.0151537
|View full text |Cite
|
Sign up to set email alerts
|

Re-Infection Outcomes Following One- And Two-Stage Surgical Revision of Infected Knee Prosthesis: A Systematic Review and Meta-Analysis

Abstract: BackgroundPeriprosthetic joint infection (PJI) is a serious complication of total knee arthroplasty. Two-stage revision is the most widely used technique and considered as the most effective for treating periprosthetic knee infection. The one-stage revision strategy is an emerging alternative option, however, its performance in comparison to the two-stage strategy is unclear. We therefore sought to ask if there was a difference in re-infection rates and other clinical outcomes when comparing the one-stage to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
165
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 243 publications
(187 citation statements)
references
References 49 publications
19
165
1
2
Order By: Relevance
“…The final results of the two stage procedure are satisfactory in terms of function, pain and eradication of infection (9.2%). Two-stage reimplantations have previously been found to successfully eradicate infection in 84-100% [1][2][3], which is consistent with our observations. A systematic review and metaanalysis based on aggregate published data found the reinfection rate after one-or two-stage revision to be approximately 8% [2].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The final results of the two stage procedure are satisfactory in terms of function, pain and eradication of infection (9.2%). Two-stage reimplantations have previously been found to successfully eradicate infection in 84-100% [1][2][3], which is consistent with our observations. A systematic review and metaanalysis based on aggregate published data found the reinfection rate after one-or two-stage revision to be approximately 8% [2].…”
Section: Discussionsupporting
confidence: 92%
“…Two-stage reimplantations have previously been found to successfully eradicate infection in 84-100% [1][2][3], which is consistent with our observations. A systematic review and metaanalysis based on aggregate published data found the reinfection rate after one-or two-stage revision to be approximately 8% [2]. Staphylococcus species were identified in about half of patients, which is consistent with findings provided by Kliushin et al [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Surgical treatments are used in conjunction with the use of powerful intravenous and oral antibiotics. After revision surgery has been performed, reinfection occurs within two years in around 8% of patients requiring further major surgery, lifelong antibiotic suppression or amputation [68]. Although PJI affects a small percentage of patients, hip and knee replacements are common and PJI is considered to be one of the most devastating complications associated with this procedure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Post-operative clinical outcomes for knee scores and range of motion were similar for both strategies. 28 Overall, it appears that the final management choice is still surgeon specific and dependent. Although no consensus has been achieved, there do appear to be some general recommendations of when not to perform a single-stage revision, as stated by Oussedik et al and shown in Table 2, which appear to be widely accepted.…”
Section: Debridement and Implant Retention (Dair)mentioning
confidence: 99%